Special issue : law and the imagining of difference - Sarat, Austin (Studies in law, politics, and society,, 2018)
Studies in Law, Politics, and Society provides a vehicle for the publication of scholarly articles within the broad parameters of interdisciplinary legal scholarship. In this latest edition of this highly successful research series, chapters examine a diverse range of legal issues and their impact on and intersections with society. This volume focusses on Law and the Imagining of Difference with each chapter examining how law responds to the claims of difference, how and when it recognizes difference and accommodates it, as well as when and why such recognition and accommodation is resisted. Topics covered include disability, same-sex marriage and gender equality. This volume brings together leading scholars and will be vital reading for all those researching in this subject area.